2017
DOI: 10.1016/j.appet.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal diabetes in utero and offspring eating behavior: The EPOCH study

Abstract: The risk of becoming overweight among offspring exposed to gestational diabetes (GDM) in utero is two-fold higher than in the general population. The responsible mechanisms are likely multifactorial, with some evidence that GDM exposure alters brain satiety signaling, which may impact eating behavior. To better understand these effects, we investigated the relationship between GDM exposure, eating behavior, and total energy intake in 268 adolescents from the Exploring Perinatal Outcomes among Children cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The detailed characteristics of the included cohort studies are listed in Table S4. In brief, 49 identified cohort studies were conducted in 14 countries, with 12 cohort studies in the United States, [20][21][22][23][24][25][26][27][28][29][30][31] 10 in China, [32][33][34][35][36][37][38][39][40][41] 4 in Canada, [42][43][44][45] 5 in Denmark, 46-50 4 in Finland, [51][52][53][54] 3 in the United Kingdom, [55][56][57] 2 in Germany, 58,59 2 in Israel, 60,61 and 1 each in Brazil, 62 Czech Republic, 63 France, 64 India, 65 Poland, 66…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed characteristics of the included cohort studies are listed in Table S4. In brief, 49 identified cohort studies were conducted in 14 countries, with 12 cohort studies in the United States, [20][21][22][23][24][25][26][27][28][29][30][31] 10 in China, [32][33][34][35][36][37][38][39][40][41] 4 in Canada, [42][43][44][45] 5 in Denmark, 46-50 4 in Finland, [51][52][53][54] 3 in the United Kingdom, [55][56][57] 2 in Germany, 58,59 2 in Israel, 60,61 and 1 each in Brazil, 62 Czech Republic, 63 France, 64 India, 65 Poland, 66…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…67 There was one multinational study with 12 countries. 68 From our sample, 6 cohort studies reported offspring overweight and/or BMI in early childhood, 20,24,[39][40][41][42] 24 cohort studies in late childhood, [21][22][23]25,26,31,[33][34][35][36][37][38][43][44][45]53,56,58,59,[63][64][65][66][67] 15 cohort studies in the pubertal period, [27][28][29][30]32,[49][50][51][52]55,57,[60][61][62]68 and 4 cohort studies in adulthood. [46][47][48]…”
Section: Andmentioning
confidence: 99%
“…Interestingly, many studies have demonstrated the effects of an in utero HFD on offspring weight, regardless of the animal model; these observations have been replicated in human MetS [38][39][40] . The exact molecular mechanism is not well defined, although DNA methylation and histone modifications seem to play a key role 38 .…”
Section: Diet-induced (Caloric Excess) Rodent Models Of Obesitymentioning
confidence: 95%
“…Comparing GDM mothers treated with lifestyle or antidiabetic agents with their non-diabetic counterparts, the linear regression analysis showed that O-GDM mothers developed their neuropsychiatric conditions at a younger age ( 94 ). Exposure to diabetes mellitus in utero also led to eating disorders in the offspring at adolescence ( 96 , 97 ). The hypothalamic blood flow in response to glucose in children of GDM mothers was obviously higher than control, combined with hypothalamic sensitivity to glucose stimulation ( 98 ).…”
Section: The Adverse Effects Of Maternal Diabetes On Offspringmentioning
confidence: 99%